VET at higher levels – an attractive option for professional careers? - Schneider, Verena [Verfasser]; Spillner, Gunther [Verfasser]; Schwarz, Henrik [Verfasser] (My University, 2023)
"The amendment of the Vocational Training Act (Berufsbildungsgesetz, BBiG) and of the Crafts and Trades Regulation Code (Handwerksordnung, HwO) in 2020 included the integration of the three level approach for advanced training occupations leading to higher level vocational education and training (VET) qualifications. For each level new standard denominations were introduced, designated as Certified Professional Specialist, Bachelor Professional and Master Professional, also in order to facilitate international connectivity. This article sheds light on the background of the amendment, presents the implementation measures that have taken place so far, and indicates some open issues." (authors' abstract; BIBB-Doku)
Keywords: S 1.5.2 Berufliche Weiterbildung; 370; Aufstiegsfortbildung; Höherqualifizierung; Bachelor Professional; Master Professional; Geprüfter Berufsspezialist; Fortbildungsabschluss; Deutscher Qualifikationsrahmen